PENGELOLAAN OBJEK WISATA PANTAI BAHARI DALAM PENINGKATAN EKONOMI MASYARAKAT DESA JAWAI LAUT KECAMATAN JAWAI KABUPATEN SAMBAS - Derlawati Derlawati; Wahab, Radimin (Jurnal Ekonomi dan Bisnis, 2025)
Tourism is one of the main sectors in driving economic growth, especially in areas with high natural tourism potential. However, many tourist attractions in Indonesia still face challenges in terms of management, inadequate infrastructure, and suboptimal promotion, so that the economic benefits for the local community are not maximized. This study aims to analyze the management of the Pantai Bahari tourist attraction in Jawai Laut Village, and how it contributes to improving the economic welfare of the local community. The research method used is a qualitative descriptive approach with data collection techniques through interviews, direct observation, and documentation. Research informants include tourism managers, village governments, local business actors, and tourists. The data obtained were analyzed using data reduction techniques, data presentation, and verification to draw valid conclusions. The results of the study showed that the management of Pantai Bahari was carried out by the Tourism Awareness Group (Pokdarwis) with a self-help and mutual cooperation approach. Although the infrastructure is still limited, this management has had a positive impact on the community's economy. The average income of the community has increased from IDR 1,200,000–IDR 1,500,000 per month before 2019 to IDR 1,800,000 in 2022. In addition, the tourism sector also creates new jobs and encourages the growth of small businesses in the trade and services sector. However, challenges such as road accessibility and lack of government support are still obstacles in the development of this tourist attraction.